Faktor-Faktor yang Berhubungan dengan Kejadian Dermatitis di Wilayah Kerja Puskesmas Tanah Tinggi Kota Binjai - Melisa Melisa; Syafran Arrazy (Poltekkes Kemenkes Jambi, 2025)
Background: Dermatitis is a skin condition caused by allergic reactions, infections, and fungal exposure, and it ranks among the ten most prevalent diseases in Binjai City from 2021 to 2024. Within the service area of the Tanah Tinggi Community Health Center, this condition ranks fourth among the ten most commonly treated illnesses over the past two years, with 2,038 reported cases in 2023 and 1,154 cases in 2024. This study aims to examine the relationship between personal hygiene, history of exposure, the physical quality of clean water, and the adequacy of waste disposal infrastructure with the occurrence of dermatitis in the Tanah Tinggi Health Center’s working area, Binjai City. Method: The research utilized a quantitative approach with an analytical observational method and adopted a cross-sectional study design. The total population in this study was 67,443 individuals, and the sampling technique employed the Lameshow formula, resulting in a total of 98 respondents. Data were collected through questionnaires and observation sheets, and subsequently analyzed using the chi-square test. Results: The analysis revealed significant associations between personal cleanliness, exposure history, physical quality of clean water, and the sufficiency of waste disposal facilities with the incidence of dermatitis. Conclusion: Therefore, it is crucial for the community to implement clean and healthy living practices, avoid excessive contact with irritants, use clean water that meets quality standards, and ensure the availability of proper waste disposal systems. The government is expected to initiate effective and sustainable programs aimed at preventing dermatitis.